2017
DOI: 10.1103/physrevb.95.205430
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical theory of anisotropic transport at LaAlO3/SrTiO3 interfaces under an in-plane magnetic field

Abstract: The unconventional magnetotransport at the interface between transition-metal oxides LaAlO 3 (LAO) and SrTiO 3 (STO) is frequently related to mobile electrons interacting with localized magnetic moments. However nature and properties of magnetism at this interface are not well understood so far. In this paper, we focus on transport effects driven by spin-orbit coupling and intentionally neglect possible strong correlations. The electrical resistivity tensor is calculated as a function of the magnitude and orie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…For small SOC, this interband scattering gets suppressed by an in-plane magnetic field leading to large negative magnetoresistance. Changing the angle of the in-plane magnetic field, we find strong angledependent current damping and a large AMR, with many angular harmonics at higher fields, as observed experimentally 30 and in previous theoretical work 23,57 .…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…For small SOC, this interband scattering gets suppressed by an in-plane magnetic field leading to large negative magnetoresistance. Changing the angle of the in-plane magnetic field, we find strong angledependent current damping and a large AMR, with many angular harmonics at higher fields, as observed experimentally 30 and in previous theoretical work 23,57 .…”
Section: Introductionsupporting
confidence: 87%
“…Our results also suggest that the AMR harmonics do not directly reflect the underlying lattice rotational symmetries of the FS. For the (001) 2DEG, our work builds upon previous important numerical studies 23,57 . Here, we further suggest simple physical mechanisms for the observations.…”
Section: Introductionmentioning
confidence: 93%
“…In combination with the Rashba SOC this produces a spin splitting at the avoided level crossing that is much larger than the one present at the zone centre. An effective tight-binding hamiltonian modelling this electronic structure and its spin texture was proposed by Diez et al [41,42] In this picture, the Rashba SOC component due to the breaking of inversion symmetry adds on top of this effect but is small. This new scenario questions the coupling of the spin to the momentum.…”
Section: Srtiomentioning
confidence: 99%
“…The dependence of C 6 on V g suggests that the higher electronic band couples strongly with the crystal sites. It would be natural to presume that the band with higher J creates stronger AMR response.Recent theoretical studies on the (100) interface have shown a strong influence of spin-orbit interactions on crystalline AMR effects [23,35,42]. FĂȘte et al have suggested that the AMR amplitude should be proportional to the square of ∆ SO /E F , where ∆ SO and E F are the Rasba spin-orbit coupling strength and the Fermi energy, respectively [23,43].…”
mentioning
confidence: 99%